Efektivitas Metode Make A Match Berbantuan LKS Terhadap Hasil Belajar PAK Kelas III SD ST Aloysius Semarang - Katerina Yesika Sara Dewantari; Sugiyana Sugiyana; F.R. Wuriningsih (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Low student learning outcomes have not reached KKM, namely 75. In this study to find out students' curiosity to learn has a positive influence on student learning outcomes in class III SD St. Aloysius Semarang, to find out the application of the LKS-assisted Make a Match learning method is effective in increasing the average learning outcomes of class III SD St. Aloysius Semarang. This type of quantitative experimental research with the true experimental design method. The research design was a pretest-posttest control group design. Data collection techniques carried out were tests, observation sheets and documentation. Analysis of the data in this study used the influence test, Independent t-test, N-Gain test, Regression and descriptive statistics. Curiosity affects learning outcomes with the acquisition of an R Square value of 83.3%. The average value of the experimental class was 79, far greater than the average of the control class, 42. The results of the calculation of the N-Gain score test showed that the average n-gain score for the Make a match method experimental class was 60.09%, including effective category. Meanwhile, the average n-gain score for the control class was 28.74%, including the less effective category. The LKS-assisted make a match method is proven to be able to improve student achievement.